2002
DOI: 10.1152/ajprenal.00080.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-protein ligase WWP2 binds to and downregulates the epithelial Na+ channel

Abstract: The epithelial Na(+) channel (ENaC) is a critical component of the pathway maintaining salt and water balance. The channel is regulated by members of the Nedd4 family of ubiquitin-protein ligases, which bind to channel subunits and catalyze channel internalization and degradation. ENaC mutations that abolish this interaction cause Liddle's syndrome, a genetic form of hypertension. Here, we test the hypothesis that WW domain-containing protein 2 (WWP2), a member of the Nedd4 family of ubiquitin-protein ligases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…We sequenced the S1P 1 -associated polypeptides from FTY720P-treated HEK293 cells by LC/MS/MS analysis. The NEDD4 family member E3 ubiquitin ligase WWP2 (25) was identified with high statistical confidence in the proteomic analysis ( Figure 3A and Table 2). To confirm the proteomic identification of WWP2, we used co-IP analysis to confirm that these 2 proteins are found in a complex.…”
Section: Phosphorylation Leads To Multisite Polyubiquitinylation Of Tmentioning
confidence: 89%
See 1 more Smart Citation
“…We sequenced the S1P 1 -associated polypeptides from FTY720P-treated HEK293 cells by LC/MS/MS analysis. The NEDD4 family member E3 ubiquitin ligase WWP2 (25) was identified with high statistical confidence in the proteomic analysis ( Figure 3A and Table 2). To confirm the proteomic identification of WWP2, we used co-IP analysis to confirm that these 2 proteins are found in a complex.…”
Section: Phosphorylation Leads To Multisite Polyubiquitinylation Of Tmentioning
confidence: 89%
“…In addition, WWP2 was capable of associating with S1P 1 -S5A and S1P 1 -K4R mutants, which suggests that phosphorylation and ubiquitinylation of the receptor are not required. Indeed, WWP2 protein contains discrete protein interaction domains such as the WW domain and a C2 domain, which could be involved in targeting the E3 ligase to membrane domains containing S1P 1 (25). A similar NEDD4 family ubiquitin E3 ligase called AIP4 targets the chemokine receptor CXCR4 for degradation (36).…”
Section: Figurementioning
confidence: 99%
“…Although the Nedd4-2-independent pathways of ENaC regulation remain unclear, it is possible that some of the genes regulated by aldosterone could act through pathways independent of Nedd4-2. Alternatively, it is possible that another WW domain-containing protein, perhaps Nedd4 or other members of Nedd4 family of HECT ubiquitin ligases, partially substitutes for the actions of Nedd4-2, albeit with less efficiency (18,24,30,31). Inactivation of mouse Nedd4 gene resulted in perinatal lethality (Cao et al, unpublished data) and therefore precluded us from assessing its role in Na ϩ homeostasis and BP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that the PY motifs interact with WW domains of a HECT (homologous to E6-AP-carboxy terminal [29]) domain-containing subfamily of E3 enzymes, the Nedd4/Nedd4-like family of ubiquitin-protein ligases (58). Specifically, binding to the WW domains of Nedd4-2 (6,11,21,25,34), Nedd4-1 (5,12,14,16,22,25,36,37,44,62,65,69), WWP1 (54), and WWP2 (48,54) was demonstrated by various approaches, suggesting that ENaC is regulated by ubiquitination. Indeed, it could be confirmed that ENaC subunits become ubiquitinated (70) and exhibit rapid turnover (47,70), a hallmark of ubiquitinated proteins.…”
mentioning
confidence: 99%